Tsetse salivary glycoproteins are modified with paucimannosidic N-glycans, are recognised by C-type lectins and bind to trypanosomes. - Radoslaw P Kozak; Karina Mondragon-Shem; Christopher Williams; Clair Rose; Samirah Perally; Guy Caljon; Jan Van Den Abbeele; Katherine Wongtrakul-Kish; Richard A Gardner; Daniel Spencer; Michael J Lehane; Álvaro Acosta-Serrano (Public Library of Science (PLoS), 2021)
African sleeping sickness is caused by Trypanosoma brucei, a parasite transmitted by the bite of a tsetse fly. Trypanosome infection induces a severe transcriptional downregulation of tsetse genes encoding for salivary proteins, which reduces its anti-hemostatic and anti-clotting properties. To better understand trypanosome transmission and the possible role of glycans in insect bloodfeeding, we characterized the N-glycome of tsetse saliva glycoproteins. Tsetse salivary N-glycans were enzymatically released, tagged with either 2-aminobenzamide (2-AB) or procainamide, and analyzed by HILIC-UHPLC-FLR coupled online with positive-ion ESI-LC-MS/MS. We found that the N-glycan profiles of T. brucei-infected and naïve tsetse salivary glycoproteins are almost identical, consisting mainly (>50%) of highly processed Man3GlcNAc2 in addition to several other paucimannose, high mannose, and few hybrid-type N-glycans. In overlay assays, these sugars were differentially recognized by the mannose receptor and DC-SIGN C-type lectins. We also show that salivary glycoproteins bind strongly to the surface of transmissible metacyclic trypanosomes. We suggest that although the repertoire of tsetse salivary N-glycans does not change during a trypanosome infection, the interactions with mannosylated glycoproteins may influence parasite transmission into the vertebrate host.